Prezența interesului public în știrile TV - Țurcanu, Dumitru (CEP USM, 2024)
The mass media, by their role and purpose, are and will definitely remain promoters of human values, of the interests of as many citizens as possible. Journalists inform the public on different platforms about the government’s actions and projects, either for the term of the mandate obtained as a result of the democratic elections, or in the short term, aiming at the realization and concrete results. The legislation from our country, as well as the international one, validated by the Moldovan authorities, provides for a series of rights and obligations of the mass media, on the one hand, and the representatives of power - on the other, in joint actions to achieve public interests, such as national security, integrity of the country, guaranteeing a decent standard of living, economic, financial and currency protection, health protection, education and culture, ecology and environmental policies and others. As a rule, even in a democratic society, the press, trying to be independent, encounters obstacles when it tries to criticize the failures of the government regarding the achievements of projects assumed to be of public interest. The analysis of three TV stations from the Republic of Moldova tries to find answers to some question marks in this summary.

Mass-media, prin rolul și menirea lor, sunt și neapărat vor rămâne promotoare ale valorilor umane, ale intereselor unui număr cât mai mare de cetățeni. Jurnaliștii informează publicul de pe diferite platforme despre acțiunile și proiectele guvernării, fie pe termenul mandatului obținut în urma alegerilor democratice, fie pe termen scurt, vizând realizarea și rezultatele concrete. Legislația de la noi din țară, cât și cea internațională, validată de autoritățile moldovenești, prevede un șir de drepturi și obligațiuni ale mass-mediei, pe de o parte, și reprezentanților puterii – pe de alta, în acțiunile comune pentru realizarea intereselor publice, cum ar fi securitatea națională, integritatea țării, garantarea unui nivel decent de viață, protejarea economică, financiară și valutară, ocrotirea sănătății, educația și cultura, ecologia și politicile de mediu și altele. De regulă, până și într-o societate democratică, presa, încercând să fie independentă, întâmpină obstacole când încearcă să critice nereușitele puterii privind realizările unor proiecte asumate de interes public. Analiza a trei posturi tv din Republica Moldova încearcă să găsească răspuns la unele semne de întrebare din acest rezumat.
THE PRESENCE OF PUBLIC INTEREST IN TV NEWS
Keywords: access to information; right to expression; public interest; international regulations; TV news; acces la informație; dreptul la exprimare; interes public; reglementări internaționale; știri tv